Preferences for redistribution and perception of fairness: An experimental study - Ruben Durante; Louis Putterman; Joël van der Weele (Brown University, Department of Economics, 2013)
We conduct a laboratory experiment to study how demand for redistribution of income depends on self-interest, insurance motives, and social concerns relating to inequality and efficiency. Our choice environments feature large groups of subjects and real world framing, and differ with respect to the source of inequality (earned or arbitrary), the cost of taxation to the decision maker, the dead-weight loss of taxation, uncertainty about own pre-tax income, and whether the decisionmaker is affected by redistribution. We estimate utility weights for the different sources of demand for redistribution, with the potential to inform modeling in macroeconomics and political economy.
Keywords: D31; P16; H24; C91; 330; income distribution; political economy; redistribution; social preferences